2012
DOI: 10.1080/15732479.2012.704051
|View full text |Cite
|
Sign up to set email alerts
|

Seismic damage detection of tall airport traffic control towers using wavelet analysis

Abstract: In this study, the applicability of continuous wavelet transform (CWT) and discrete wavelet transform (DWT) for seismic damage detection of tall airport traffic control (ATC) towers was investigated. Nonlinear finite element (NFE) model of Kuala Lumpur International Airport (KLIA) ATC tower with the height of 120 m was created using discrete moment-curvature hinges. Three different strong ground motions excited the tower and three different damage scenarios were then obtained. Response accelerations at four st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Kaloop and Hu (2016) proved that the energy of DWT has higher performance in damage detection than CWT due to lower correlation coefficient values. Also, sensitivity to stiffness change by DWT is more than CWT (Vafaei and Adnan, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Kaloop and Hu (2016) proved that the energy of DWT has higher performance in damage detection than CWT due to lower correlation coefficient values. Also, sensitivity to stiffness change by DWT is more than CWT (Vafaei and Adnan, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…They concluded that the method could identify the time of occurrence and roughly the spatial distribution and degree of the major damage in the imperial county services (ICS) building. Vafaei and Adnan [32] investigated the applicability of the continuous wavelet transform (CWT) and discrete wavelet transform (DWT) to seismic damage detection of tall airport traffic control towers, numerically proving that CWT could successfully detect seismic damage even with noise-polluted signals. Aguirre et al [33] explored the feasibility of using output-only model-free wavelet-based techniques for damage detection in reinforced concrete structures subjected to seismic excitations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they can provide more detailed information than conventional Fourier analysis because Fourier transform projects the signal in the frequency domain and has no link with the time domain. In addition, the Fourier transform is limited to stationary signals [11]. However, wavelet analysis has the power to analyze the non-stationary structural dynamic responses.…”
Section: Introductionmentioning
confidence: 99%